Mejora de la calidad de vida en un complejo residencial mediante la identificación de los criterios prácticos de los espacios públicos educativos - Shakeri, Mousa; Arjmand, Atefeh (Innovaciencia, 2019)
Introduction: One of the approaches to improve life quality in a residential complex is by modifying them properly to an educational public space. An educational public space is consisted of three factors: individual, community and physical space, the important factor in these environments are, the proper individual and general education and respecting the natural or artificial surroundings. Based on the probabilistic approach, an environment can have a direct impact on an individual. An environment can teach us cultural, moral and social values. The purpose of this study is to identify the criteria for designing educating public spaces in a residential complex to improve the environmental quality. Therefore, the qualitative data was collected with the help of library documents in two categories: Residential Satisfaction Factors and Educational Public Spaces Criteria. Then, both groups were adapted based on content validity and a questionnaire was used to collect quantitative data. The questionnaires were distributed among the architecture professors, according to the Delphi method. SPSS 18 software was used to analyze the quantitative data to prioritize and correlate the criteria and micro criteria for designing educational public spaces in the residential complex. The results indicate that among all of the criteria for an educational public space, safety is more important than other criteria, in a residential complex, the top five criteria are as follows: health and safety, aesthetics, social -cultural interactions, and national-local identity. Therefore, it can be concluded that by applying the micro criteria of the aforementioned criteria in the communal spaces of residential complexes, the quality of residential environment can be improved.